2018
DOI: 10.1002/casp.2351
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and stressful life events among homeless people in Madrid (Spain)

Abstract: The article describes a study carried out with a representative sample of homeless people in Madrid (Spain; N = 188). This study aims to corroborate the relationship identified in the literature between stressful life events and suicidal behaviour in a group in a situation of social exclusion, to assess the differences in the number and characteristics of stressful life events experienced by homeless people who are attempters and non‐attempters, and to identify which combination of stressful life events enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 50 publications
3
52
0
4
Order By: Relevance
“…Some other relevant studies have been conducted worldwide, including a study in China (18,19), a population-based study in Denmark (12), and a study in the USA (11). Also, most of the studies in western countries have examined SLEs in SAs (3,12,20), whereas the current study explored both suicide and SAs. The same results were found in the present study and Paul and Wang studies in the USA (18,21), as well as in a meta-analysis study (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some other relevant studies have been conducted worldwide, including a study in China (18,19), a population-based study in Denmark (12), and a study in the USA (11). Also, most of the studies in western countries have examined SLEs in SAs (3,12,20), whereas the current study explored both suicide and SAs. The same results were found in the present study and Paul and Wang studies in the USA (18,21), as well as in a meta-analysis study (22).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are more cases of physical and sexual abuse among people experiencing homelessness than in the domiciled population (Wenzel et al, 2000). Moreover, among this population, SLEs are associated with the presence of a wide range of physical and mental health problems (Hatch & Dohrenwend, 2007), a reduction in the quality of life (Krug, 2004), suicide attempts (Panadero et al, 2018), and high rates of substance abuse (Tyler & Melander, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a high prevalence of childhood SLEs in people experiencing homelessness (Edalati et al, 2016;Stein et al, 2002). Studies conducted on both European and US-based samples have shown that these individuals often present indicators of dysfunctional home backgrounds, with a history of physical and/or sexual abuse in childhood, parental substance abuse or mental illness, running away from home, and institutionalization (Padgett et al, 2012;Panadero et al, 2018;Wong & Piliavin, 2001). In addition, it has been found that exposure to adversity during childhood and adolescence is the main trigger for leaving home and early homelessness (Mar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A particularly striking figure is that more than half of those interviewed who had been mothers said they had attempted suicide. This is a much higher percentage than the figure for people living homeless in Madrid (Panadero et al, 2018) and for women living homeless (Vázquez & Panadero, 2019). Most of the suicide attempts had occurred prior to the person concerned becoming homeless.…”
Section: Discussionmentioning
confidence: 68%
“…Women living homeless have to cope with multiple intersecting vulnerabilities (e.g. extreme poverty, lack of social networks, physical and mental health problems, experiencing multiple and serious stressful life events at an early age, consumption of psychoactive substances and difficulties in accessing the labour market), some of which are specific to their status as a woman, for example, sexual assaults, sexual exploitation, gender‐based violence, unwanted pregnancies and abortions (Belcher, Greene, McAlpine, & Ball, 2001; Guillén et al, 2020; Hatch & Dohrenwend, 2007; Herman, Susser, Struening, & Link, 1997; Panadero, Martín, & Vázquez, 2018; Vázquez et al, 2017b; Vázquez, Panadero, & Pascual, 2019; Vázquez & Panadero, in press). Unfortunately, the way in which a person experiences a disadvantage is inevitably determined by the other disadvantages they suffer from.…”
Section: Introductionmentioning
confidence: 99%